2019
DOI: 10.1111/jgs.15808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monthly High‐Dose Vitamin D on Mental Health in Older Adults: Secondary Analysis of a RCT

Abstract: OBJECTIVES To test the effect of monthly high‐dose vitamin D supplementation on mental health in pre‐frail older adults. DESIGN Ancillary study of a 1‐year double‐blind randomized clinical trial conducted in Zurich, Switzerland. SETTING AND PARTICIPANTS A total of 200 community‐dwelling adults 70 years and older with a prior fall event in the last year. Participants were randomized to receive 24 000 IU vitamin D3 (considered standard of care), 60 000 IU vitamin D3, or 24 000 IU vitamin D3 plus 300 μg calcifedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…Regarding dosage, a recent RCT [162] tested whether 50 µg per day (2000 IU) is more effective than 20 µg (800 IU) vitamin D 3 for improving cognitive performance among relatively healthy adults aged ≥60 years (31% 25(OH)D < 50 nmol/l (20 ng/mL)), but found comparable results in both groups over a 24-month treatment period and no significant improvement in either group. Similarly, another recent RCT found that supplementing older adults with a history of falling (58% 25(OH)D < 50 nmol/l (20 ng/mL)) with 600 µg (24,000 IU) vitamin D 3 , 1500 µg (60,000 IU) vitamin D 3 or a combination of 600 µg (24,000 IU) vitamin D 3 with calcifediol once per month also led neither to different effects in mental health within one year, nor to any significant improvement [163]. Participants achieving the highest serum 25(OH)D levels (112.5-247.5 nmol/l (45-99 ng/mL)), however, had a "small, clinically uncertain but statistically significant improvement in mental health scores", irrespective of the supplement dose.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding dosage, a recent RCT [162] tested whether 50 µg per day (2000 IU) is more effective than 20 µg (800 IU) vitamin D 3 for improving cognitive performance among relatively healthy adults aged ≥60 years (31% 25(OH)D < 50 nmol/l (20 ng/mL)), but found comparable results in both groups over a 24-month treatment period and no significant improvement in either group. Similarly, another recent RCT found that supplementing older adults with a history of falling (58% 25(OH)D < 50 nmol/l (20 ng/mL)) with 600 µg (24,000 IU) vitamin D 3 , 1500 µg (60,000 IU) vitamin D 3 or a combination of 600 µg (24,000 IU) vitamin D 3 with calcifediol once per month also led neither to different effects in mental health within one year, nor to any significant improvement [163]. Participants achieving the highest serum 25(OH)D levels (112.5-247.5 nmol/l (45-99 ng/mL)), however, had a "small, clinically uncertain but statistically significant improvement in mental health scores", irrespective of the supplement dose.…”
Section: Discussionmentioning
confidence: 92%
“…Supporting a causal role for vitamin D in mental health is a 2019 randomized clinical trial of vitamin D supplementation for 1 year in 200 older (aged ≥70 years) adults who experienced a fall in the previous year; there were significant improvements in mental health (the Mental Component Summary of the Short Form Health Survey 36‐item patient health survey) in the groups achieving the highest vitamin D levels at 12 months 37 and strongest in those who were deficient at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…low vitamin D and increased PTH levels increase inflammation, which is a risk factor for depression) (41) . Fourth, although no beneficial effect of higher monthly doses of vitamin D compared with the standard monthly dose is known (43) , several studies have evaluated the effects of vitamin D supplementation on depression (44,45) . Finally, although these studies did not support a causal effect on any of the disease outcomes, multiple Mendelian randomisation studies have investigated the putative causal association of vitamin D on multiple health outcomes, especially in preventing or controlling depression and major depressive disorder (46,47) .…”
Section: Interpretation Of Findingsmentioning
confidence: 99%